Preparation method and application method of magnetic composite visible light catalytic material

By synthesizing the magnetic composite visible photocatalytic material CuFeO2/g-C3N4/CoZnAl-LDH, the problem of difficult pollution in water is difficult to remove, efficient removal and self-cleaning of catalytic materials is achieved, and environmentally friendly and economical advantages are achieved.

CN119838620APending Publication Date: 2025-04-18XINJIANG UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411801420.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently remove pollution from new bromine flame retardants (NBFRs) in low concentrations in water, and toxic by-products may be produced during photocatalysis.

Method used

The magnetic composite visible photocatalytic material CuFeO2/g-C3N4/CoZnAl-LDH was synthesized by a one-step low-temperature solvent thermal method. Through its excellent adsorption and photocatalytic properties, it efficiently removes NBFRs pollution in water and realizes self-cleaning of the catalytic material.

Benefits of technology

The efficient removal of low-concentration NBFRs in water is achieved. The photocatalytic regeneration can be driven by visible light, and the material is strongly stable, and the efficiency does not decrease significantly after 5 recycle use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838620A_ABST
    Figure CN119838620A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of water pollution control, and relates to a preparation method and an application method of a magnetic composite visible light catalytic material. The preparation method of the magnetic composite visible light catalytic material comprises the following steps: S1, preparing graphite-phase carbon nitride nanosheets from melamine and urea; s2, dispersing the graphite phase carbon nitride nanosheets into ethanol, dropwise adding into a mixed solution of copper nitrate and ferric nitrate, and obtaining a delafossite and graphite phase carbon nitride composite material after the reaction is finished; and S3, mixing the delafossite and graphite phase carbon nitride composite material with cobalt nitrate, zinc nitrate and aluminum nitrate solutions, and reacting to obtain the composite visible light catalytic material. The composite material prepared by the invention has excellent adsorption and photocatalytic performance, and can have a good removal effect on low-concentration NBFRs pollution in water, and visible light is adopted for photocatalytic regeneration to drive a photocatalytic reaction, so that the method is a sustainable and environment-friendly NBFRs pollution treatment method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of water pollution control, and in particular relates to a preparation method of a magnetic composite visible light catalytic material and an application method thereof. Background Art

[0002] Brominated flame retardants (BFRs) are a class of synthetic bromine-containing organic compounds with excellent flame retardant properties. They are often used to improve the fire resistance and safety of products, such as electronic products, carpets, textiles, furniture, etc. Due to the threats of persistence, long-range migration, high bioaccumulation, and high toxicity, traditional brominated flame retardants such as polybrominated diphenyl ethers (PBDEs) and hexabromocyclododecane (HBCD) have been included in the list of strictly controlled persistent organic pollutants (POPs) in the Stockholm Convention and are strictly prohibited in many countries and regions. Therefore, new brominated flame retardants (NBFRs), such as decabromodiphenylethane (DBDPE), bis(2-ethylhexyl)-3,4,5,6-tetrabromophthalate (TBPH), hexabromobenzene (HB B), and 2,3,4,5,6-pentabromotoluene (PBT) are mass-produced and widely used in consumer products to replace the banned traditional brominated flame retardants. Similar to traditional BFRs, most NBFRs are additive flame retardants that do not form strong covalent bonds with materials, causing the products to release NBFRs into the natural environment during production, consumption and disposal. At present, NBFRs have been detected in almost all environmental media (atmosphere, dust, water, sediment, soil, etc.), as well as a large number of biological samples (such as birds, fish, poultry), and even human samples (such as serum and breast milk). Many studies have shown that NBFRs have toxic effects similar to PBDEs, such as liver toxicity, endocrine disruption, developmental toxicity, behavioral toxicity, etc. In addition, due to the low polarity, high lipophilicity and poor biodegradability of NBFRs, they exhibit bioaccumulation and biomagnification effects in some species, posing potential risks to the ecological environment and human health. Therefore, it is urgent to develop practical technologies to treat NBFRs in water environments.

[0003] Photocatalytic oxidation technology is one of the most promising advanced oxidation technologies for treating organic pollutants and is widely used for the complete removal of organic pollutants in water. NBFRs contain electron-rich benzene rings and bromine atoms, are sensitive to light, and can be photodegraded under sunlight, especially under ultraviolet light, but their photodegradation process in natural water environments is quite slow and may produce toxic byproducts such as brominated dibenzofuran and dioxins. Therefore, efficient photocatalytic technology can be developed to treat NBFRs pollution in water. The photocatalytic degradation of organic pollutants mostly occurs on the surface of the photocatalyst, and the adsorption capacity of the photocatalyst limits the effect of photocatalytic degradation of organic pollutants. NBFRs are typical non-ionic hydrophobic organic compounds with low concentrations in water, resulting in a low probability of contact with the photocatalyst, thereby limiting the catalytic effect of the photocatalyst. Therefore, the present invention proposes a strategy for designing a catalytic material with excellent adsorption and photocatalytic function coupling, which is used to efficiently remove low-concentration NBFRs pollution in water, and can also achieve self-cleaning of the catalytic material through the photocatalytic process.

[0004] Layered double hydroxide (LDH) materials are a class of clay minerals formed by a network of divalent and trivalent metal cations, with hydroxide anions and exchangeable anions between the layers. They are widely used as efficient adsorbents for removing heavy metal ions and organic pollutants due to their large surface area, good structural stability and excellent electronic structure. However, LDH has a wide band gap, low electron / hole separation efficiency and fast recombination, which limits its application in photocatalysis. Graphitic carbon nitride (g-C3N4) is a widely used n-type semiconductor photocatalyst with advantages such as a wide spectral absorption range, good thermal stability and easy synthesis, but it also has disadvantages such as a wide band gap, low visible light utilization efficiency and fast electron / hole recombination. Copper iron ore (CuFeO2) is a p-type photocatalyst with excellent characteristics such as a narrow band gap, high conduction band (CB) reduction energy, large hole mobility, high stability and low cost. However, low conductivity and high electron / hole recombination rate still limit its photocatalytic performance and application.

[0005] Therefore, it is urgent to develop catalytic materials with both efficient adsorption and photocatalytic properties to control low-concentration NBFRs pollution in water. Summary of the invention

[0006] In order to solve the above problems, the object of the present invention is to provide a method for preparing a magnetic composite visible light catalytic material and an application method thereof.

[0007] In order to achieve the above objectives, the embodiments of the present invention provide the following technical solutions:

[0008] According to a first aspect of an embodiment of the present invention, a method for preparing a magnetic composite visible light catalytic material is provided, comprising the following steps:

[0009] S1, mixing melamine and urea and calcining at high temperature in a nitrogen atmosphere to obtain graphite phase carbon nitride nanosheets;

[0010] S2, dispersing the graphite phase carbon nitride nanosheets obtained in step S1 in ethanol, then dropping them into a mixed solution of copper nitrate and ferric nitrate, and then adjusting the pH of the mixed solution to 11.0-13.0, and washing and drying after the reaction to obtain a delafossite and graphite phase carbon nitride composite material;

[0011] S3. Disperse the delafossite and graphite-phase carbon nitride composite material in ethanol, and then mix with cobalt nitrate, zinc nitrate and aluminum nitrate solutions. After the reaction is completed, wash with deionized water and dry to obtain the magnetic composite visible light catalytic material (Cu FeO2 / g-C3N4 / CoZnAl-LDH) of delafossite, graphite-phase carbon nitride and cobalt-zinc-aluminum layered double metal hydroxide.

[0012] Furthermore, in step S1, the melamine and urea are mixed in a molar ratio of 3:1, and the temperature of the high-temperature calcination is 550°C.

[0013] Furthermore, in step S2, the concentration of ethanol is 5 to 20 g / L.

[0014] Furthermore, in step S2, the reaction temperature is 180° C. and the reaction time is 12 hours.

[0015] Furthermore, in step S2, the molar ratio of copper nitrate to iron nitrate is 1:1, the mass ratio of graphite carbon nitride nanosheets to copper nitrate is 5.5:1, and the mass ratio of graphite carbon nitride nanosheets to iron nitrate is 4.5:1.

[0016] Furthermore, in step S3, the delafossite and graphite-phase carbon nitride composite material is dispersed in ethanol to a concentration of 5 to 20 g / L.

[0017] Furthermore, in step S3, the molar ratio of cobalt nitrate, zinc nitrate and aluminum nitrate is 1:1:1, and the mass ratio of delafossite and graphite phase carbon nitride composite material to cobalt nitrate, zinc nitrate and aluminum nitrate is 2:1:1:1.

[0018] Furthermore, in step S3, the reaction temperature is 180° C. and the reaction time is 6 hours.

[0019] Furthermore, in step S3, the drying is performed in a vacuum drying oven at a temperature of 60°C.

[0020] According to a second aspect of an embodiment of the present invention, there is provided a method for applying the magnetic composite visible light catalytic material prepared by the above method in the preparation of a brominated flame retardant, comprising the following steps:

[0021] (1) Mixing the magnetic composite visible light photocatalytic material prepared by the above method with the NBFRs solution, continuously shaking and evenly mixing in the dark, taking samples at regular intervals, monitoring the concentration change of NBFRs in the solution, and calculating the adsorption amount of the magnetic composite visible light photocatalytic material, wherein the addition concentration of the magnetic composite visible light photocatalytic material is 0.05-0.1 g / L, the solution pH is 3.0-11.0, and the initial concentration of NBFRs is 0.2-20 μmol / L;

[0022] (2) Evaluate the photocatalytic degradation of NBFRs and self-cleaning performance of the magnetic composite visible light catalytic material under visible light: After the CuFeO2 / g-C3N4 / CoZnAl-LDH composite material reaches the adsorption equilibrium of NBFRs, it is collected by a magnet and dispersed in deionized water. It is then placed in a photocatalytic reactor with a xenon lamp as the light source and a 400 nm cutoff filter. Samples are taken at regular intervals at room temperature, and the concentration of NBFRs in the system is detected by a gas chromatograph to calculate its degradation rate;

[0023] (3) The NBFRs pollutant is the brominated flame retardant, and the brominated flame retardant includes any one or a combination of two or more of bis(2-ethylhexyl)-3,4,5,6-tetrabromophthalate (TBPH), hexabromobenzene (HBB), 2,3,4,5,6-pentabromotoluene (PBT), and decabromodiphenylethane (DBDPE).

[0024] Compared with the prior art, the advantages of the embodiments of the present invention are:

[0025] The present invention provides a method for preparing a magnetic composite visible light catalytic material and an application method thereof.

[0026] (1) The composite material prepared by the present invention has excellent adsorption and photocatalytic properties, and can effectively remove low-concentration NBFRs pollution in water. The photocatalytic regeneration can be driven by visible light, which is a sustainable and environmentally friendly method for treating NBFRs pollution.

[0027] (2) The composite material obtained by the present invention has a large specific surface area and porosity, and has excellent adsorption performance for the new brominated flame retardant; in addition, the composite material has a wide light absorption range, high visible light utilization rate, a narrow band gap width, and a low recombination rate of electrons and holes, and can generate superoxide anion free radicals and singlet oxygen active substances, and thus also has excellent photocatalytic performance for the new brominated flame retardant;

[0028] (3) The present invention adopts a one-step low-temperature solvothermal method to synthesize the CuFeO2 / g-C3N4 / CoZnAl-LDH composite material, which has simple method, low energy consumption, low raw material cost, and can be synthesized in the laboratory and can be used for large-scale industrial production;

[0029] (4) The composite material prepared by the present invention has strong stability, can be recycled for 5 times without significant decrease in adsorption and photocatalytic efficiency, has low cost of use, and has important practical significance and value. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. Moreover, the same reference symbols are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:

[0031] Figure 1 is a scanning electron microscope image of the four synthesized materials.

[0032] Figure 2a Fourier transform infrared spectra of g-C3N4, CuFeO2 / g-C3N4, CoZnAl-LDH and CuFeO2 / g-C3N4 / CoZnAl-LDH.

[0033] Figure 2b N2 adsorption and desorption isotherms of g-C3N4, CuFeO2 / g-C3N4, CoZnAl-LDH and CuFeO2 / g-C3N4 / CoZnA l-LDH.

[0034] Figure 3a This is the full spectrum of the X-ray photoelectron energy spectrum of the magnetic composite visible light catalytic material of the present invention.

[0035] Figure 3b This is a detailed spectrum of the X-ray photoelectron spectrum C1s of the magnetic composite visible light catalytic material of the present invention.

[0036] Figure 3c This is a fine spectrum of the X-ray photoelectron spectrum N1s of the magnetic composite visible light catalytic material of the present invention.

[0037] Figure 3d This is a detailed spectrum of Co 2p in the X-ray photoelectron spectrum of the magnetic composite visible light catalytic material of the present invention.

[0038] Figure 3e This is a detailed spectrum of Zn 2p in the X-ray photoelectron spectrum of the magnetic composite visible light catalytic material of the present invention.

[0039] Figure 3f This is a fine spectrum of Al 2p in the X-ray photoelectron spectrum of the magnetic composite visible light catalytic material of the present invention.

[0040] Figure 3gThis is a detailed Cu 2p spectrum of the X-ray photoelectron spectrum of the magnetic composite visible light catalytic material of the present invention.

[0041] Figure 3h This is a detailed spectrum of Fe 2p in the X-ray photoelectron spectrum of the magnetic composite visible light catalytic material of the present invention.

[0042] Figure 3i This is a detailed spectrum of the X-ray photoelectron spectrum O1s of the magnetic composite visible light catalytic material of the present invention.

[0043] Figure 4a UV-visible diffuse reflectance spectra of g-C3N4, CuFeO2 / g-C3N4, CoZnAl-LDH and CuFeO2 / g-C3N4 / CoZnAl-LDH.

[0044] Figure 4b Schematic diagram of the band gap energy of g-C3N4, CuFeO2 / g-C3N4, CoZnAl-LDH and CuFeO2 / g-C3N4 / CoZnAl-LDH.

[0045] Figure 5a The adsorption curves of 2 μmol / L TBPH on four materials.

[0046] Figure 5b is the initial concentration of TBPH.

[0047] Figure 5c The effect of solution pH on the adsorption performance of the magnetic composite visible light catalytic material of the present invention.

[0048] Figure 5d It is the adsorption capacity (Qm) of the magnetic composite visible light catalytic material of the present invention for TBPH, HBB and PBT.

[0049] Figure 6a Photocatalytic degradation of TBPH adsorbed on synthetic materials under ultraviolet irradiation.

[0050] Figure 6b Photocatalytic degradation of TBPH adsorbed on the synthetic material under visible light (λ>400nm).

[0051] Figure 6c is the debromination rate of TBPH on the composite material under UV light irradiation.

[0052] Figure 6d This is a five-cycle process of adsorption and photocatalytic degradation of TBPH on the magnetic composite visible light photocatalytic material of the present invention.

[0053] Figure 7a DMPO- ·OH electron paramagnetic resonance spectrum signal diagram.

[0054] Figure 7b DMPO- · O 2- Electron paramagnetic resonance spectroscopy signal diagram.

[0055] Figure 7c The TEMP- 1 O2 electron paramagnetic resonance spectrum signal diagram.

[0056] Figure 7d TEMPO-h is the magnetic composite visible light catalytic material of the present invention. + Electron paramagnetic resonance spectroscopy signal diagram. DETAILED DESCRIPTION

[0057] In view of the deficiencies in the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution, its implementation process and principle will be further explained as follows.

[0058] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.

[0059] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.

[0060] The embodiment of the present invention provides a method for preparing a magnetic composite visible light catalytic material, comprising the following steps:

[0061] S1, mixing melamine and urea in a molar ratio of 3:1 and calcining at high temperature in a nitrogen atmosphere to obtain graphite phase carbon nitride nanosheets; the temperature of the high temperature calcination is 550° C.;

[0062] S2, dispersing the graphite phase carbon nitride nanosheets obtained in step S1 into ethanol, and then dropping them into a mixed solution of copper nitrate and ferric nitrate, and then adjusting the pH of the mixed solution to 11-13, and washing and drying after the reaction to obtain a composite material of delafossite and graphite phase carbon nitride; the concentration of the ethanol is 5-20 g / L; the reaction temperature is 180° C., and the reaction time is 12 hours; wherein the molar ratio of copper nitrate to ferric nitrate is 1:1, the mass ratio of graphite phase carbon nitride nanosheets to copper nitrate is 5.5:1, and the mass ratio of graphite phase carbon nitride nanosheets to ferric nitrate is 4.5:1;

[0063] S3. Dispersing the delafossite and graphite-phase carbon nitride composite material in ethanol, and then mixing with cobalt nitrate, zinc nitrate and aluminum nitrate solutions. After the reaction is completed, washing with deionized water and drying to obtain a composite material of delafossite, graphite-phase carbon nitride and cobalt-zinc-aluminum layered double hydroxide (CuFeO2 / g-C3N4 / CoZnAl-LDH); the concentration of the delafossite and graphite-phase carbon nitride composite material after being dispersed in ethanol is 5-20 g / L; the molar ratio of cobalt nitrate, zinc nitrate and aluminum nitrate is 1:1:1, and the mass ratio of the delafossite and graphite-phase carbon nitride composite material to cobalt nitrate, zinc nitrate and aluminum nitrate is 2:1:1:1; the reaction temperature is 180°C, and the reaction time is 6 hours; the drying is carried out in a vacuum drying oven at a temperature of 60°C.

[0064] According to a second aspect of an embodiment of the present invention, there is provided a method for applying the magnetic composite visible light catalytic material prepared by the above method in the preparation of a brominated flame retardant, comprising the following steps:

[0065] (1) Mixing the magnetic composite visible light photocatalytic material prepared by the above method with the NBFRs solution, continuously shaking and evenly mixing in the dark, taking samples at regular intervals, monitoring the concentration change of NBFRs in the solution, and calculating the adsorption amount of the magnetic composite visible light photocatalytic material, wherein the addition concentration of the magnetic composite visible light photocatalytic material is 0.05-0.1 g / L, the solution pH is 3.0-11.0, and the initial concentration of NBFRs is 0.2-20 μmol / L;

[0066] (2) Evaluate the photocatalytic degradation of NBFRs and self-cleaning performance of the magnetic composite visible light catalytic material under visible light: After the CuFeO2 / g-C3N4 / CoZnAl-LDH composite material reaches the adsorption equilibrium of NBFRs, it is collected by a magnet and dispersed in deionized water. It is then placed in a photocatalytic reactor with a xenon lamp as the light source and a 400 nm cutoff filter. Samples are taken at regular intervals at room temperature, and the concentration of NBFRs in the system is detected by a gas chromatograph to calculate its degradation rate;

[0067] (3) The NBFRs pollutant is the brominated flame retardant, and the brominated flame retardant includes any one or a combination of two or more of bis(2-ethylhexyl)-3,4,5,6-tetrabromophthalate (TBPH), hexabromobenzene (HBB), 2,3,4,5,6-pentabromotoluene (PBT), and decabromodiphenylethane (DBDPE).

[0068] In order to better understand the technical solution of the present invention, it is described in detail below in conjunction with specific embodiments.

[0069] Example 1: Synthesis of g-C3N4.

[0070] Melamine and urea were mixed in a molar ratio of 3:1, calcined at 550°C for 3 hours under a nitrogen atmosphere (99.9%), and ground into powder in a mortar after cooling to room temperature. Then, the ground sample was calcined again at 550°C for 2 hours under a nitrogen atmosphere (99.9%). After that, the cooled sample was washed three times with ethanol, dried, ground, and sieved through a 200-mesh stainless steel mesh for the next experiment and synthesis.

[0071] Example 2: Synthesis of CuFeO2 / g-C3N4.

[0072] CuFeO2 / g-C3N4 was prepared by a one-step low-temperature solvothermal method. The obtained g-C3N4 was dispersed in ethanol and added dropwise to a mixed solution of copper nitrate and ferric nitrate. The pH of the mixed solution was adjusted to 12, and the mixture was reacted at 180°C for 12 hours. After washing and drying, a composite material of delafossite and graphite phase carbon nitride (g-C3N4 / CuFeO2) was obtained. The molar ratio of copper nitrate to ferric nitrate was 1:1, and the mass ratio of graphite phase carbon nitride to copper nitrate and ferric nitrate was 5.5:1 and 4.5:1, respectively. ;

[0073] Example 3: Synthesis of CuFeO2 / g-C3N4 / CoZnAl-LDH.

[0074] CuFeO2 / g-C3N4 / CoZnAl-LDH was prepared by a one-step low-temperature solvothermal method. The g-C3N4 / CuFeO2 composite material dispersed in ethanol was mixed with cobalt nitrate, zinc nitrate and aluminum nitrate solutions, reacted at 180°C for 6 hours, washed with deionized water and dried to obtain a composite material of g-C3N4, CuFeO2 and cobalt-zinc-aluminum layered double hydroxide (g-C3N4 / CuFeO2 / CoZnAl-LDH). The mass ratio of the g-C3N4 / CuFeO2 composite material to cobalt nitrate, zinc nitrate and aluminum nitrate was 2:1:1:1.

[0075] Example 4: Scanning electron microscopy characterization of the synthetic materials of Examples 1-3.

[0076] SEM images of g-C3N4 materials ( Figure 1a ) shows that g-C3N4 presents a two-dimensional sheet structure with wrinkles. After g-C3N4 material is compounded with CuFeO2, it presents a thin film structure, and CuFeO2 is evenly distributed on the surface of g-C3N4 nanosheets ( Figure 1b The original CoZnAl-LDH is composed of well-dispersed nanosheets ( Figure 1c ). Figure 1d It shows that CoZnAl-LDH is vertically embedded in CuFeO2 / g-C3N4, resulting in additional wrinkles and protrusions of g-C3N4 in the CuFeO2 / g-C3N4 / CoZnAl-LDH composite.

[0077] Example 5: Infrared spectrum and specific surface area characterization of the synthetic materials of Examples 1-3.

[0078] Figure 2a Fourier transform infrared spectra of g-C3N4, CuFeO2 / g-C3N4, CoZnAl-LDH and CuFeO2 / g-C3N4 / CoZnAl-LDH are shown. Except for CoZnAl-LDH, the Fourier transform infrared spectra of g-C3N4, CuFeO2 / g-C3N4 and CuFeO2 / g-C3N4 / CoZnAl-LDH are -1 and 1200~1650cm -1 There are characteristic peaks at 3000-3500cm, which are related to the characteristic bending vibration of tri-s-triazine unit and the typical stretching vibration of CN bond in aromatic amine heterostructure, respectively, confirming the successful synthesis of g-C3N4 and its composite with CuFeO2 and CoZnAl-LDH. In addition, due to the presence of -OH (hydrophilic) groups and adsorbed water molecules, all infrared spectra show peaks at 3000-3500cm -1 In the infrared spectra of CoZnAl-LDH and CuFeO2 / g-C3N4 / CoZnAl-LDH, the peaks in the range of 400-800 cm -1 Typical absorption bands at 560cm -1 and 700cm -1 The two characteristic absorption peaks at 1357 cm-1 are attributed to the stretching and bending vibrations of MO and M-OH (M = Co, Zn and Al). -1 The strong absorption peak at belongs to CO3 2- Asymmetric stretching vibration.

[0079] Figure 2bThe N2 adsorption-desorption isotherms of g-C3N4, CuFeO2 / g-C3N4, CoZnAl-LDH and CuFeO2 / g-C3N4 / CoZn Al-LDH are shown. According to the classification of the International Union of Pure and Applied Chemistry (IUPAC), they all belong to the typical type IV adsorption with H3 type hysteresis, indicating that all the prepared materials are mesoporous adsorption materials. Among the four prepared materials, CuFeO2 / g-C3N4 / CoZnAl-LDH has the largest BET surface area (79.5 m 2 / g) and pore volume (0.1635cm 3 / g), which indicates that the composite material can provide more adsorption sites for the adsorption of NBFRs.

[0080] Example 6: X-ray photoelectron spectroscopy characterization of the synthetic materials of Examples 1-3.

[0081] Figure 3 shows the XPS analysis of the surface element composition and chemical state of the CuFeO2 / g-C3N4 / CoZnAl-LDH composite material. In the full scan spectrum of the composite material ( Figure 3a ) All elements including C, N, Co, Zn, Al, Cu, Fe, and O were observed, confirming the tight coupling between the three components (CuFeO2, g-C3N4, and CoZnAl-LDH). C 1s spectrum ( Figure 3b ) contains five decomposition peaks at 284.64eV, 285.2eV, 288.7eV, 287.3eV and 291.8eV, which correspond to graphite carbon (26.06%), C-NH2 (21.76%), N=CN (17.09%), CO (32.00%) and C=O (3.09%). Among them, the appearance of CO and C=O is usually due to the CO3 2- In the N 1s high-resolution spectrum ( Figure 3c ), the three peaks with binding energies of 397.84 eV, 398.78 eV and 400.17 eV are considered to be CN=C, N-(C)3 and C-NH2 structures. For the high-resolution spectrum of Co 2p ( Figure 3d ), the pair of peaks at 781.26eV and 796.9eV are considered to be Co 2+ , while the satellite peaks at 786.02eV and 804.3eV indicate the presence of high-spin divalent Co in CuFeO2 / g-C3N4 / CoZnAl-LDH. 2 + Compared with pure CoZnAl-LDH, Co 2p 3 / 2 and Co 2p 1 / 2 The binding energy of Co2+ The coordination environment of Zn2p is changed due to the generation of defects. The two peaks near 1021.58eV and 1044.67eV belong to Zn2p 3 / 2 and Zn 2p 1 / 2 ( Figure 3e ). In addition, Al 3+ The binding energy of Figure 3f The Cu 2p high-resolution spectrum can be divided into two peaks, located at 932.44 eV (Cu2p 3 / 2 ) and 952.37 eV (Cu 2p 1 / 2 )( Figure 3g ). About Fe 2p high resolution spectrum ( Figure 3h ), two groups of Fe 2p were observed at 711.6eV, 724.8eV and 716.2eV, 733.6eV, respectively. 3 / 2 、Fe 2p 1 / 2 and its satellite peaks, corresponding to Fe in CuFeO2 / g-C3N4 / CoZnAl-LDH 3+ . O 1s spectrum ( Figure 3i ) has four fitting peaks at 530 eV, 530.9 eV, 531.7 eV and 532.8 eV, corresponding to metal oxides (20.44%), OH (33.25%), C=O (36.60%) and COC (9.71%), respectively.

[0082] Example 7: Characterization of the photocatalytic properties of the synthetic materials of Examples 1-3.

[0083] According to the UV-visible diffuse reflectance spectra of the four synthetic materials ( Figure 4a ) shows that the light absorption edge of g-C3N4 is at 450nm. In contrast, the CuFeO2 / g-C3N4 composite has a wider light absorption range, which means that the interaction between CuFeO2 and g-C3N4 can significantly improve the light harvesting ability. In addition, due to the metal cation (Co 2+ 、Zn 2+ and Al 3+ ), CoZnAl-LDH showed absorption in the ultraviolet region from 200nm to 280nm and in the visible region from 450nm to 680nm. The CuFeO2 / g-C3N4 / CoZnAl-LDH composite material showed the widest light absorption range among all prefabricated materials, indicating that it has the strongest light absorption ability, which is mainly attributed to the combination of CuFeO2 and g-C3N4 on CoZnAl-LDH-, which expands the light absorption region of the composite material. In addition, Figure 4bAs shown, according to the Kubelka-Munk equation, the band gaps of g-C3N4, CoZnAl-LDH, CuFeO2 / g-C3N4 and CuFeO2 / g-C3N4 / CoZnAl-LDH are 2.67eV, 2.13eV, 1.88eV and 1.56eV, respectively, indicating that the CuFeO2 / g-C3N4 / CoZnAl-LDH composite material has the smallest band gap and the strongest photocatalytic performance.

[0084] Example 8: Adsorption properties of synthetic materials.

[0085] Figure 5a The adsorption process of TBPH by four synthetic materials is shown. After reaching adsorption equilibrium in 30 min, the removal rates of g-C3N4, CuFeO2 / g-C3N4, CoZnAl-LDH and CuFeO2 / g-C3N4 / CoZnAl-LDH for TBP H were 40.2±0.4%, 67.6±10.5%, 86.1±1.9% and 97.0±0.0%, respectively. Among these materials, g-C3N4 had the worst adsorption performance for TBPH. The adsorption capacity of the CuFeO2 / g-C3N4 composite material was significantly improved. The adsorption performance of CoZnAl-LDH was better than that of the CuFeO2 / g-C3N4 composite material, which was mainly due to the larger specific surface area and more adsorption sites of CoZnAl-LDH. The CuFeO2 / g-C3N4 / CoZnAl-LDH composite material showed the best adsorption performance, and 97.0% of TBP H could be adsorbed and removed within 30 min.

[0086] Figure 5b The effect of the initial concentration of TBPH (0.2, 2.0, 10.0 and 20.0 μmol / L) on the adsorption performance of the synthetic material is shown. As the initial concentration of TBPH increases from 0.2 μmol / L to 10.0 μmol / L, the adsorption removal rate of TBPH by Cu FeO2 / g-C3N4 / CoZnAl-LDH gradually increases from 73.1% to 98.0%. However, when the initial concentration increases to 20.0 μmol / L, the adsorption rate gradually decreases to 96.0%. This is mainly due to the fact that the low concentration of TBPH has a smaller chance of colliding with the adsorption sites of the composite material, resulting in a lower removal rate of TBPH. As the concentration of TBPH increases, the adsorption sites of the adsorbent are gradually occupied and saturated. When the concentration increases again, the adsorption rate decreases, so more adsorbents are needed to remove higher concentrations of TBPH.

[0087] Figure 5cThe adsorption performance of CuFeO2 / g-C3N4 / CoZnAl-LDH composite materials on NBFRs under different pH conditions (3.0-11.0) was shown. The results showed that the CuFeO2 / g-C3N4 / CoZnAl-LDH composite material exhibited good adsorption performance in a wide pH range of 3.0-11.0, and could achieve a removal rate of 92.7±1.8% for TB pH under all pH treatments, indicating that the pH condition (3.0-11.0) had little effect on the adsorption performance of the composite material. In addition, Figure 5d The saturated adsorption capacity of the composite material for three NBFRs. It can be seen that the CuFeO2 / g-C3N4 / CoZnAl-LDH composite material exhibits excellent performance in the adsorption of three NBFRs (TBPH, HBB and PBT), and the saturated adsorption capacities of TBPH, HBB and PBT are 2240 mg / g, 1997 mg / g and 2054 mg / g, respectively.

[0088] Example 9: Photocatalytic and regeneration performance of CuFeO2 / g-C3N4 / CoZnAl-LDH composite material.

[0089] The CuFeO2 / g-C3N4 / CoZnAl-LDH composite material has excellent performance in photocatalytic degradation of NBFRs under ultraviolet and visible light irradiation. Specifically, under ultraviolet irradiation ( Figure 6a ), the photodegradation of TBPH in the blank group (without material) was slow, and the removal rate was 81.4±0.1% at 60 minutes, which was mainly the direct photolysis process of TBPH. Although the CoZnAl-LDH material also has good adsorption performance for TBPH, its photocatalytic degradation effect on TBPH is not satisfactory. Only 72.7±2.0% of TBPH was photodegraded in 60 minutes, which is lower than the treatment group treated with ultraviolet light only (without material) and the CuFeO2 / g-C3N4 / CoZnAl-LDH treatment group. This is mainly because the light scattering and shielding effect of the CoZnAl-LDH material with weaker photocatalytic ability reduced the photon absorption efficiency of TBPH, resulting in a decrease in the removal rate of TBPH. When the CuFeO2 / g-C3N4 / CoZnAl-LDH composite material was introduced, the TB PH adsorbed on the surface was almost completely degraded (99.5±0.1% removal rate) within 60 minutes under ultraviolet light irradiation. In the treatment with visible light irradiation only (λ>400nm) ( Figure 6b ), no photodegradation of TBPH was observed, indicating that the rapid degradation of TBPH was mainly attributed to irradiation in the UV region (λ<400nm) ( Figure 6a). After 60 minutes of visible light irradiation, only 6.4±0.0% of TBPH adsorbed on the CoZnAl-LDH material was degraded, while under visible light, CuFeO2 / g-C3N4 / CoZnAl-LDH photocatalytically degraded 96.0±0.2% of TBPH, indicating that the CuFeO2 / g-C3N4 / Co Zn Al-LDH composite material has excellent photocatalytic activity even under visible light. In addition, the debromination rate of TBPH by the CuFeO2 / g-C3N4 / CoZnAl-LDH composite material under UV irradiation was measured ( Figure 6c ), after 120 minutes of UV irradiation, the debromination rate reached 95.5%, indicating that the composite material has satisfactory photocatalytic debromination performance. Figure 6d The experimental results of the recycling of the composite material show that after five adsorption-photocatalytic cycles, the removal ability of the CuFeO2 / g-C3N4 / CoZnAl-LDH composite material for TBPH did not decrease significantly, indicating that the composite material has excellent stability and reusability.

[0090] Example 10: Photocatalytic mechanism of CuFeO2 / g-C3N4 / CoZnAl-LDH composite material.

[0091] Electron paramagnetic resonance spectrometer was used to analyze the type and intensity of free radicals generated by CuFeO2 / g-C3N4 / CoZnAl-LDH composite materials under light irradiation. As shown in Figure 7, CuFeO2 / g-C3N4 / CoZnAl-LDH composite materials can generate superoxide anion free radicals ( · O 2- ), singlet oxygen ( 1 O2) and holes (h + ) of these three active substances, while no hydroxyl radicals ( · OH) production, indicating that in the process of CuFeO2 / g-C3N4 / CoZnAl-LDH composite material photocatalytic degradation of NBFRs, the main · O 2- , 1 O2 and H + These three active substances participate in and promote the degradation of NBFRs.

[0092] The embodiments described above are only for illustrating the preferred implementation of the present invention. It should be pointed out that, for ordinary technicians in this field, several improvements can be made without departing from the scope of protection of this patent, and these improvements should also be regarded as within the scope of protection of this patent.

Claims

1. A method for preparing a magnetic composite visible light catalytic material, characterized in that: The following steps are involved: S1, mixing melamine and urea and calcining at high temperature in a nitrogen atmosphere to obtain graphite phase carbon nitride nanosheets; S2, dispersing the graphite phase carbon nitride nanosheets obtained in step S1 in ethanol, then dropping them into a mixed solution of copper nitrate and ferric nitrate, and then adjusting the pH of the mixed solution to 11.0-13.0, and washing and drying after the reaction to obtain a delafossite and graphite phase carbon nitride composite material; S3, dispersing the delafossite and graphite phase carbon nitride composite material in ethanol, and then mixing with cobalt nitrate, zinc nitrate and aluminum nitrate solutions, and washing with deionized water and drying after the reaction to obtain the magnetic composite visible light photocatalytic material.

2. The method for preparing the magnetic composite visible light catalytic material according to claim 1, characterized in that: In step S1, the melamine and urea are mixed in a molar ratio of 3:1, and the temperature of the high-temperature calcination is 550°C.

3. The method for preparing the magnetic composite visible light catalytic material according to claim 1, characterized in that: In step S2, the concentration of ethanol is 5-20 g / L.

4. The method for preparing the magnetic composite visible light catalytic material according to claim 1, characterized in that: In step S2, the reaction temperature is 180° C. and the reaction time is 12 hours.

5. The method for preparing the magnetic composite visible light catalytic material according to claim 1, characterized in that: In step S2, the molar ratio of copper nitrate to iron nitrate is 1:1, the mass ratio of graphite carbon nitride nanosheets to copper nitrate is 5.5:1, and the mass ratio of graphite carbon nitride nanosheets to iron nitrate is 4.5:

1.

6. The method for preparing the magnetic composite visible light catalytic material according to claim 1, characterized in that: In step S3, the delafossite and graphite-phase carbon nitride composite material is dispersed in ethanol to a concentration of 5 to 20 g / L.

7. The method for preparing the magnetic composite visible light catalytic material according to claim 1, characterized in that: In step S3, the molar ratio of cobalt nitrate, zinc nitrate and aluminum nitrate is 1:1:1, and the mass ratio of delafossite and graphite phase carbon nitride composite material to cobalt nitrate, zinc nitrate and aluminum nitrate is 2:1:1:

1.

8. The method for preparing the magnetic composite visible light catalytic material according to claim 1, characterized in that: In step S3, the reaction temperature is 180° C. and the reaction time is 6 hours.

9. The method for preparing the magnetic composite visible light catalytic material according to claim 1, characterized in that: In step S3, the drying is performed in a vacuum drying oven at a temperature of 60°C.

10. A method for using the magnetic composite visible light catalytic material prepared by the method according to any one of claims 1 to 9 in the preparation of brominated flame retardants, characterized in that: The following steps are involved: (1) Mixing the magnetic composite visible light photocatalytic material prepared by the method according to any one of claims 1 to 9 with a NBFRs solution, continuously shaking and evenly mixing in the dark, taking samples at regular intervals, monitoring the concentration change of NBFRs in the solution, and calculating the adsorption amount of the magnetic composite visible light photocatalytic material, wherein the added concentration of the magnetic composite visible light photocatalytic material is 0.05 to 0.1 g / L, the solution pH is 3.0 to 11.0, and the initial concentration of NBFRs is 0.2 to 20 μmol / L; (2) Evaluate the photocatalytic degradation of NBFRs and self-cleaning performance of the magnetic composite visible light catalytic material under visible light: After the CuFeO2 / g-C3N4 / CoZnAl-LDH composite material reaches the adsorption equilibrium of NBFRs, it is collected by a magnet and dispersed in deionized water. It is then placed in a photocatalytic reactor with a xenon lamp as the light source and a 400 nm cutoff filter. Samples are taken at regular intervals at room temperature, and the concentration of NBFRs in the system is detected by a gas chromatograph to calculate its degradation rate; (3) The NBFRs pollutant is the brominated flame retardant, and the brominated flame retardant includes any one or a combination of two or more of bis(2-ethylhexyl)-3,4,5,6-tetrabromophthalate (TBPH), hexabromobenzene (HBB), 2,3,4,5,6-pentabromotoluene (PBT), and decabromodiphenylethane (DBDPE).